Complications in otolaryngology : head and neck surgery - Bernal-Sprekelsen, Manuel (Thieme, 2013)
"For all specialists and trainees performing otolaryngology-head and neck surgery, knowledge of potential complications is integral to successful procedures. Complications in Otolaryngology fills an important gap in the field by examining complications in all areas related to otolaryngology and head and neck surgery outside of facial plastic and aesthetic surgery. From procedures in the middle and inner ear, paranasal sinuses, and salivary glands, to endoscopic skull base surgery, to airway management, laryngectomy, thyroid surgery, and much more, the book is a practical reference for the busy surgeon. Special Features: The first complete, one-volume source on risks and complications in otology, rhinology, and head and neck surgery, Written by a team of leading worldwide authorities, who share tips, tricks, pearls, and clinical experience in every instructive chapter, Formatted for easy accessibility, including a definition of each complication and its sequelae, incidence of occurrence, point during surgery when it is most likely to happen, tips for avoiding it, and techniques for managing it. Includes current scientific, evidence-based information throughout. Generously illustrated, with more than 400 full-color, intraoperative photographs and endoscopic images to help readers visualize surgical problems and solutions for every case, including revision surgery. For the increasing number of ENT and neurosurgical teams who perform advanced endoscopic surgery of the anterior skull base beyond the paranasal sinuses, this book contains valuable information on complications not available elsewhere. It is essential reading for all surgeons who need to prepare for and manage every contingency for the best possible outcomes in otolaryngology and head and neck surgical procedures"--Provided by publisher.